Qualitative Evaluation of Baduanjin (Traditional Chinese Qigong) on Health Promotion among an Elderly Community Population at Risk for Ischemic Stroke - Zheng, Guohua (Evid Based Complement Alternat Med, 2015)
Background. Baduanjin is a traditional Chinese qigong that has been practiced for a long time in China as a mind-body exercise in community elderly populations. The objective of this study was to qualitatively evaluate the perceived benefit of regular Baduanjin qigong in community elders. Methods. A total of 20 participants who had completed the 12-week Baduanjin qigong training were interviewed regarding their perceived effect on physical and psychological health and whether Baduanjin qigong was suitable for the elderly. Results. Almost all participants agreed that Baduanjin qigong could promote their multisystem or organ functions (e.g., digestive and circulatory systems), increase their immunity, make their bodies relax, and improve their mood and confidence. Most of the participants also agreed that Baduanjin qigong was appropriate for elderly individuals. Few individuals felt bored because of an hour Baduanjin training each day. Conclusions. The findings suggest that regular Baduanjin qigong may be potentially helpful to promote the overall physical and psychological health of elderly community populations and may be useful and feasible as a body-mind exercise in the health promotion in the elderly community populations.